2020
DOI: 10.1002/pa.2497
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing grocery online in a nonmetro city: Investigating the role of convenience, security, and variety

Abstract: This study targets consumers of a nonmetro city to assess their perceptions about online grocery shopping. Earlier grocery companies were targeting only selected metro cities. However, recent reports have indicated that nonmetro cities can also become a profitable market for online grocery retailers. This study is an attempt to provide an empirical analysis related to the beliefs and the attitude of target consumers about online grocery shopping. By applying belief-attitude-behavior approach, the study tests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Where EE is concerned, several studies explicitly show that the expected effort level and perceived complexity of using online grocery services are significantly negatively related to future buying intentions [35,[37][38][39][40][41][42][43][44][45][46]. As for SI, the role of the perceived opinion of important reference groups such as friends, colleagues, and family has been confirmed in both qualitative [45,47] and quantitative studies [39,[48][49][50][51][52]. Evidence on the impact of FC, however, is less clear-cut.…”
Section: Utaut Constructsmentioning
confidence: 99%
“…Where EE is concerned, several studies explicitly show that the expected effort level and perceived complexity of using online grocery services are significantly negatively related to future buying intentions [35,[37][38][39][40][41][42][43][44][45][46]. As for SI, the role of the perceived opinion of important reference groups such as friends, colleagues, and family has been confirmed in both qualitative [45,47] and quantitative studies [39,[48][49][50][51][52]. Evidence on the impact of FC, however, is less clear-cut.…”
Section: Utaut Constructsmentioning
confidence: 99%
“…Khan and Khan (2020) [26] stated that convenience is very crucial in online shopping. The convenience factor refers to the situation in which it is easier to search for information online compared to conventional stores.…”
Section: Product Attributesmentioning
confidence: 99%
“…Their findings concluded that consumers use e-grocery services to save Grocery shopping through e-grocery apps saves consumers time as they do not have to think about the travel time to the market or physical supermarket and consumers do not have to spend time standing in a long queue while grocery shopping. Time-related indicators are measured on factors or variables such as convenience, utilitarian motives and perceived time pressure which can be found in these research [38], [40], [42]- [44], [46], [47], [52].…”
mentioning
confidence: 99%